Structurally simplified GCMO crossbar design for artificial synaptic networks - Antola, Anni; Angervo, Ilari; Huhtinen, Hannu; Miettinen, Mikko; Schulman, Alejandro; Paturi, Petriina (American Institute of Physics, 2025)
Harnessing the full power of memristors as artificial synapses demands a simple and scalable crossbar architecture enabling their seamless integration into diverse applications. This Letter presents the 3 × 3 memristor crossbar array configuration featuring a grid of interconnected devices. The composition includes Al as the reactive top electrode connecting the device columns and Gd1−xCaxMnO3 (GCMO, x = 0.8 ) serving as the bottom electrode connecting the device rows as well as the memristive material eliminating the need for additional layers and fabrication steps. Controlled-sized vias through insulating the Al2O3 layer connect the electrodes forming the active interface. The idea is validated with a test sample of 3 × 3 crossbars with the Au/GCMO/Al structure, Au enabling Ohmic contact to GCMO, with device resistive switching ratios mostly around 102 and yield of over 90%. The devised crossbar structure could provide a highly scalable, yet simple, geometry suitable for synaptic networks.